The Impact of Online Gambling Intensity on Anxiety, Stress, and Depression in Adolescents in Cilegon City: A Social and Education Approach - Ahmad Jauharuddin; Nurdiyanto Nurdiyanto (Universitas Muhammadiyah Enrekang, 2025)
The phenomenon of online gambling among adolescents in Cilegon City continues to rise and is linked to mental health problems. However, empirical evidence on how much the intensity of play influences anxiety, stress, and depression remains limited. This causal-comparative quantitative study involved 30 adolescents aged 15–21 selected through purposive sampling. Participants were divided into two groups: 15 “occasional” and 15 “frequent” online gamblers. Instruments were 4-point Likert-scale questionnaires measuring anxiety (α = 0.763), stress (α = 0.745), and depression (α = 0.781); item validity met the criterion r > 0.3. Data were analyzed with MANOVA using SPSS 31.0. MANOVA revealed a significant simultaneous effect (Wilks’ Lambda = 0.176; F = 13.004; p < 0.001). Follow-up tests showed strong effects of intensity on anxiety (F = 31.136; η² = 0.536), stress (F = 15.942; η² = 0.368), and depression (F = 20.806; η² = 0.424). Mean scores on all three psychological aspects were significantly higher in the “frequent play” group. These findings align with previous studies emphasizing that repeated exposure to financial and social risks in online gambling increases adolescents’ cognitive–emotional burden, with effect contributions up to 53.6 % indicating intensity as a primary predictor. The more frequently adolescents engage in online gambling, the higher their levels of anxiety, stress, and depression become. Family, school, and digital-regulation-based interventions are needed to prevent further psychopathological impacts.